Pilot study: Effects of parenteral glutamine dipeptide supplementation on neutrophil functions and prevention of chemotherapy-induced side-effects in acute myeloid leukaemia patients - Chuleegone Sornsuvit (2018)
The effect of parenteral glutamine dipeptide (Gln) supplementation on neutrophil phagocytosis, superoxide anion generation (SAG), prevention of chemotherapy-induced side-effects and cost-effectiveness was examined in a pilot study of acute myeloid leukaemia (AML) patients receiving chemotherapy. Sixteen AML patients were randomized to receive intravenous supplementation with Gln (30 g/day) or an equivalent quantity (25 g/day) of a standard amino acid mixture (control) on days 1 - 5 of chemotherapy. Complete blood count was evaluated twice a week until hospital discharge, and neutrophil phagocytosis and SAG were measured when absolute neutrophil count reached > 500/ μl. Patients were observed for development of infection, mucositis and diarrhoea. In Gln-treated patients, the percentage of neutrophil phagocytosis and the SAG levels were significantly higher than in control patients (20.5 ± 6.0% and 18.9 ± 2.9 nmol/106neutrophils per 10 min, respectively). The Gln-treated patients lost significantly less weight, tended to have shorter in-patient duration and had less severe oral mucositis than controls. This pilot study provides preliminary indication that parenteral Gln supplementation enhances neutrophil phagocytic function, maintains nutritional status and is cost effective. Parenteral Gln may also prevent oral musositis, although further studies involving more patients need to be undertaken to confirm this and the other results. Copyright © 2008 Field House Publishing LLP.